Gender and Governance: Exploring Women's Leadership in Private Higher Education in Gorontalo - Tety Thalib; Asna Aneta; Zulaecha Ngiu; Juriko Abdussamad (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to explore the dynamics of women's leadership in the governance of private universities in Gorontalo Province, focusing on the challenges, strategies, and their contributions to the quality of management of higher education institutions. Although the discourse of gender equality is increasingly strengthening in the world of education, the representation of women in strategic positions is still relatively limited. A qualitative approach was used with a case study method through in-depth interviews, participant observation, and document review in a number of private universities in Gorontalo. The results of the study indicate that women leaders have high adaptive capacity, build collaborative leadership models, and play an important role in driving institutional innovation. However, they still face various structural barriers, including gender stereotypes, patriarchal culture, and lack of internal policy support. This study concludes that empowering women's leadership not only has an impact on more inclusive and responsive governance, but also on improving the academic quality and governance of universities as a whole. The implications of these findings encourage the need for affirmative policies and institutional cultural transformation to strengthen participation in higher education leadership structures.